QUALITY CHARACTERISTICS OF HERBAL TEA WITH DIFFERENT RATIOS OF PANDAN (Pandanus amaryllifolius) and STEVIA (Stevia rebaudiana) LEAVES - Lestari, Suji; Pato, Usman; Hasnah AR, Nur; Defri, Ifwarisan; Rahmayani, Irma; Yunita, Imelda; Hasibuan, Ahmad Ibrahim Roni Surya (SAGU, 2026)
The primary objective of this study was to evaluate the effect of varying ratios of pandan leaves (Pandanus amaryllifolius) and stevia leaves (Stevia rebaudiana) on the chemical and sensory characteristics of herbal tea, identifying the optimal formulation relative to SNI 3945:2016 standards. Unlike traditional tea derived from Camellia sinensis, herbal infusions utilize diverse plant materials valued for their therapeutic properties. Pandan leaves, in particular, contain essential bioactive compounds—including polyphenols, alkaloids, saponins, tannins, and flavonoids—that provide significant antimicrobial and antioxidant  benefits. The experiment was conducted using a completely randomized design with four treatments and  four replications. The treatments consisted of different ratios of pandan to stevia leaves: 60:40 (PS1), 65:35  (PS2), 70:30 (PS3), and 75:25 (PS4). The observed parameters included moisture content, ash content,  antioxidant activity, total polyphenols, and sensory evaluation (color, aroma, taste, and overall acceptance).  Data were analyzed using analysis of variance (ANOVA) followed by Duncan’s multiple range test  (DMRT) at a 5% significance level. The results showed that the ratio of pandan and stevia leaves  significantly affected moisture content, ash content, antioxidant activity, total polyphenols, and sensory  attributes. The best treatment was PS1 (60:40), which exhibited 6.35% moisture content, 7.08% ash  content, antioxidant activity of 21.75 ppm, and total polyphenols of 84.34 mg GAE/g. Sensory evaluation  indicated that the product had a characteristic pandan aroma, slightly bitter taste, and slightly greenish  color, with acceptable overall preference by panelists.